Building networks and partnerships - Worley, Christopher G.; Mirvis, Philip H., 1951- (Emerald, 2013)
Organizing for Sustainable Effectiveness highlights research and practice aimed at understanding how organizations and more inclusive systems of actors develop a continuous, unfaltering focus on sustainability. It will examine how they organize to achieve expanded purposes, the associated changes in purpose and governance, relationships among various stakeholders, boundaries between organizations and other elements of the environment in which they operate, organizational systems and processes, leadership, competencies and capabilities. Thus sustainability is seen as entailing a continuous dynamic adaptive process in people, organizations and systems, striving to be as proactive as possible, moving upstream in improving and developing organizational processes and issues.
Keywords: Organizational effectiveness.; Business networks.; elektronické knihy; electronic books